Numerical Study of the Wide‐angle Polarization‐Independent Ultra‐Broadband Efficient Selective Solar Absorber in the Entire Solar Spectrum (Solar RRL 7∕2017). Issue 7 (July 2017) - Wu, Dong; Liu, Yumin; Xu, Zenghui; Yu, Zhongyuan; Yu, Li; Chen, Lei; Liu, Chang; Li, Ruifang; Ma, Rui; Zhang, Jinqiannan; Ye, Han
Abstract : Increasing the absorption efficiency of solar radiation has great significance for the renewable energy applications, such as residential water heating, seawater desalination, wastewater treatment and solar thermophotovoltaic devices. However, the near‐ideal solar thermal absorbers have not yet been demonstrated, which has a near unity absorption from the ultraviolet to the near‐infrared region and meanwhile an absorption close to zero in the mid‐infrared region. Here (article No.201700049 ), using the FEM and FDTD methods respectively, we propose and numerically demonstrate an efficient selective solar absorber, which has an extremely high absorption above 99% at the range of 435 nm‐1520 nm and a low emission below 20% at the range beyond 2500 nm. The total photothermal conversion efficiency of the proposed solar absorber can reach as high as 91.53%, which is very close to the photothermal conversion efficiency of the ideal cut‐off absorber. Owing to the characteristics such as polarization and angle independence, broadband operation, nearperfect absorption and strong spectral selectivity, the solar absorbers are promising candidates for solar energy harvesting, stealth technology, and thermo‐photovoltaic energy conversion.